PROSPECTIVES OF HOMOLJE AS AN ECO-DESTINATION - Babić, Vedrana; Lačnjevac, Časlav (Economics of Agriculture, 2018)
Homolje with its own heterogeneous and attractive tourist potential, correspond important tourist area of Eastern Serbia. Relief is represented with hills and plains. Climate is moderate continental. Hydrograph is represented by river Mlava with her tributaries. This community is full with different animal and herbal species. Economy is undeveloped, but natural and anthropogenic fortune, peace, silence, green nature, loveliness of housekeeper, etc., is important potential for development of rural tourism. Text of roads showing possibilities of sustainable development in area of Homolje, like new possibility for progress in this area. Authors of this work were data collection trough experience on terrain, area monitoring and benchmarking. Homolje can be important eco destination in tourist map of Serbia.